The deep-sea Anguilliformes and Saccopharyngiformes (Teleostei: Elopomorpha) collected on the Brazilian continental slope, between 11o and 23o S - Melo, Marcelo R. S.; Nunan, Gustavo W. A.; Braga, Adriana C.; Costa, Paulo A. S. (Zootaxa, 2009)
A review of the deep-sea anguilliform and saccopharyngiform eels collected by the French R/Vs Marion Dufresne (1987), Thalassa (1999, 2000), and the Brazilian Astro Garoupa (2003) revealed a great diversity of these groups on the Brazilian continental slope (11–23 o S, 19–40 o W), in the depth range of 233 to 3450 m. Of the 33 species collected, 13 (39.4%) are being reported for the first time in the western South Atlantic. New taxa are represented by one species recently described and few other are probably undescribed. The most species-rich family in the area was Synaphobranchidae (11 species), followed by Congridae (9), Nettastomatidae (5), Nemichthyidae (3), Serrivomeridae (2), Colocongridae (1), Cyematidae (1), and Eurypharyngidae (1). Regarding the vertical species distribution, a gradual transition of species was observed, without any clear break along the slope.